Genome-wide analyses reveal intricate genetic mechanisms underlying egg production efficiency in chickens - Lizhi Tan; Xinyu Cai; Yuan Kong; Zexuan Liu; Zilong Wen; Lina Bu; Yuzhan Wang; Xiaojun Liu; Zhiwu Zhang; Jianlin Han; Dandan Wang; Yiqiang Zhao (Journal of Animal Science and Biotechnology)
Abstract Background Compared to many other vertebrates, chickens have a high reproductive efficiency in terms of egg production. The classic traits for evaluating egg-laying performance include age at first egg, egg number, clutch size, laying rate, etc. These egg-laying traits were not specifically designed to characterize egg production efficiency and stability. By considering the stage-specific variations in the egg production curve, this study aims to investigate the genetic mechanisms that directly influence the efficiency of egg production at each stage of the laying cycle. Results Using whole-genome sequencing data, we perform comprehensive genome-wide association study for 39 traits that focus on egg production efficiency and stability in the Gushi chicken. We showed that the haplotype-based approach is more effective for genetic mapping and capturing polygenic architecture. By combining the signals of Singleton Density Score (SDS), which is a population-genetic statistic designed to detect recent selection by leveraging the distribution of singletons, and association analyses, multiple egg-laying traits related to egg production efficiency were found to have experienced polygenic selection. Consistently, functional analysis of associated genes demonstrates that egg production efficiency benefits from multiple physiological functions. Furthermore, our results identified the CNNM2 gene, known for its role in magnesium homeostasis, plays a dual role in egg production variance, promoting variability during the up-stage while reducing it during the sustained-stage to optimize egg production efficiency. Conclusions Collectively, our multiple genome analyses reveal a complex genetic mechanism underlying more efficient and stable egg production, and establish chicken genetics as a model for studying reproductive efficiency across species.